Circulating Immune Complexes in the Serum in Systemic Lupus Erythematosus and in Carriers of Hepatitis B Antigen QUANTITATION BY BINDING TO RADIOLABELED Clq - Nydegger, Urs E. (1974)
A sensitive and reproducible procedure for the detection of soluble immune complexes in sera from patients with various immunopathological disorders is reported. Radiolabeled C1q is reacted with sera containing immune complexes. Separation of free from complex bound [(125)I]C1q is achieved by selective precipitation with polyethylene glycol (PEG). The method is based on both the large molecular size and the C1q-binding property characterizing immune complexes. The minimal amount of aggregated immunoglobulins thus detected is about 10 μg and that of soluble human IgG-anti-IgG complexes is about 3 μg of complexed antibody. Some immune complexes formed in large antigen excess (Ag(2)Ab) can still be detected by this radiolabeled C1q binding assay. The specificity of the radiolabeled C1q binding test was documented by the inability of antigen-F(ab′)(2) antibody complexes to lead to a precipitation of [(125)I]C1q in PEG. In a second step, this radiolabeled C1q binding assay was applied to an experimental model of immune complex disease and was shown to be efficient for the detection of in vivo formed immune complexes. Finally, the technique could be applied to the study of sera from patients with systemic lupus erythematosus (SLE) or to carriers of the hepatitis B antigen (HB-Ag). Significantly increased [(125)I]-C1q binding values were observed in 52 sera from SLE patients when compared to values obtained with healthy blood donors (P<0.001). Particularly high values were seen in active disease, a finding which was confirmed by follow-up studies performed with four SLE patients. No increased [(125)I]C1q binding was seen in 18 healthy carriers of the HB-Ag; whereas, sera from carriers with hepatitis appear to precipitate increased [(125)I]C1q percentages: 7/24 cases with acute transient and 4/7 cases with chronic persistent hepatitis were found to increasingly bind [(125)I]C1q. The results were also used for a correlative study of [(125)I]C1q binding to IgG levels in the sera but increased [(125)I]C1q binding could not be attributed to high serum IgG levels which are likely to account for gammaglobulin aggregates. These examples suggest the utility of the radiolabeled C1q binding assay for the evaluation of immune complex diseases in human pathology.